Dynamic modelling and start-up operation of a solar-assisted recompression supercritical CO2 Brayton power cycle. (1st August 2017) - Luu, Minh Tri; Milani, Dia; McNaughton, Robbie; Abbas, Ali
Highlights: Investigated the operation of sCO2 Brayton cycle in transient conditions. Start-up to full-load scheme for a solar-assisted recompression cycle is developed. The scheme consists of four consecutive phases with distinct control events. Flexible heat sources (fossil fuel, solar energy) can be used during the start-up. Initial cooler by-passing is a vital event for sustaining supercritical condition. Abstract: In this paper, we propose and analyse a start-up scheme that can be used to bring a solar-assisted recompression sCO2 Brayton cycle from cold-start to full-load operation (i.e. design point). For this purpose, a comprehensive dynamic model for the entire solar integrated process is developed. It is found that the proposed scheme (consisting of four consecutive operational phases) can successfully bring the cycle to full-load operation in-line with the peak hours of solar energy harvesting. This scheme is featured with the flexibility of using fossil fuel and/or solar energy when appropriate process controls are in place. By utilising the CO2 pressure-temperature-density diagram, an effective strategy is developed and integrated with the start-up scheme for guiding the cycle through the transient period and sustaining the supercritical phase. During full-load operation, there can be unexpected incidents, e.g. loss of charge (LOC). It is found that the LOC event decreases the CO2 cumulative mass of the cycle and consequently reduces the overall solar energy utilization of the system. The sCO2 recompression Brayton cycle intrinsically shows high tolerance to the loss of CO2, thus the supercritical phase can mostly be sustained during a possible LOC event.